Implementasi Program Pusat Pelayanan Kesejahteraan Anak Integratif (Ppkai) Di Kabupaten Gowa - St. Nurhijriah St. Nurhijriah; Budi Setiawati; Rulinawaty Kasmad (Department of Public Administration, Muhammadiyah University of Makassar, 2018)
The results of the study show that the implementation of the Integrative Child Welfare Service Center program in Gowa regency. The method of the research is descriptive qualitative. The kind of the implementation that used in the research is Sorean c winter type that consist of three indicators, they are organizational and inter-organizational behavior, street level bureaucrat behavior and target group behavior. The technique of data collection consists of observation, interview and documentation which researcher did around three months. The results of the study show that the implementation of the Integrative Child Welfare Service Center program in Gowa regency is seen from the organizational and inter-organizational behavior, namely the maximum commitment, while the coordination has not been maximized. Lower level bureaucrat behavior is seen from policy discretion which is still lacking and has not gone well. The behavior of the target group is seen from the positive response, namely the target group strongly supports the program but the negative response is that there are still many who are not aware of the existence of a child welfare service center program because there is but a fail of socialization carried out and the absence of a complaint secretariat at the sub-district or village level. Keywords: policy implementation, Behavior, Servis, PPKAI program, integrative children. ABSTRAKPenelitian ini bertujuan untuk mengetahui implementasi program pusat pelayanan kesejahteraan anak integratif di Kabupaten Gowa. Metode penelitian yang digunakan adalah kualitatif yang bertipe deskriptif. Model implementasi yang digunakan dalam penelitian ini adalah model Sorean C. Winter yang terdiri dari 3 Indikator yaitu, perilaku organisasi dan antar organisasi, perilaku birokrat level bawah dan perilaku kolompok sasaran. Adapun teknik pengumpulam data meliputi observasi, wawancara dan dokumentasi. Hasil penelitian menunjukkan bahwa implementasi program Pusat Pelayanan Kesejahteraan Anak Integratif di Kabupaten Gowa dilihat dari, perilaku organisasi dan antar organisasi dilihat dari komitmen sudah maksimal sedangkan koordinasi yang dilakukan belum maksimal. Perilaku birokrat level bawah dilihat dari diskresi kebijakan, masih kurang dan belum berjalan dengan baik. Perilaku kelompok sasaran dilihat dari respon positifnya yaitu kelompok sasaran sangat mendukung adanya program tersebut tetapi respon negatifnya yaitu masih banyak yang belum mengetahui adanya program pusat pelayanan kesejahteraan anak karena masih kurangnya sosialisasi yang dilakukan dan tidak adanya sekretariat aduan pada tingkat Kecamatan atau Desa. Kata Kunci: Implementasi Kebijakan, Pelayanan, Perilaku, Program PPKAI, Anak Integratif